2021
DOI: 10.5194/hess-25-1727-2021
|View full text |Cite
|
Sign up to set email alerts
|

Hydraulic shortcuts increase the connectivity of arable land areas to surface waters

Abstract: Abstract. Surface runoff represents a major pathway for pesticide transport from agricultural areas to surface waters. The influence of artificial structures (e.g. roads, hedges, and ditches) on surface runoff connectivity has been shown in various studies. In Switzerland, so-called hydraulic shortcuts (e.g. inlet and maintenance shafts of road or field storm drainage systems) have been shown to influence surface runoff connectivity and related pesticide transport. Their occurrence and their influence on surfa… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 40 publications
0
11
0
Order By: Relevance
“…While we could not find a conclusive explanation for such long delays for this small catchment, the sharp peaks pointed to the regular occurrence of losses from hard surfaces such as roads and farmyards. Hydraulic shortcuts as recently described ( Schönenberger & Stamm, 2021 ) may play an important role in these contexts. Indeed, local observations revealed substantial concentrations in tile drains.…”
Section: Discussionmentioning
confidence: 71%
See 1 more Smart Citation
“…While we could not find a conclusive explanation for such long delays for this small catchment, the sharp peaks pointed to the regular occurrence of losses from hard surfaces such as roads and farmyards. Hydraulic shortcuts as recently described ( Schönenberger & Stamm, 2021 ) may play an important role in these contexts. Indeed, local observations revealed substantial concentrations in tile drains.…”
Section: Discussionmentioning
confidence: 71%
“…The more plausible flow paths were through surface runoff over impervious surfaces and drainage network for which it is less likely the physical and chemical properties play a role in the temporal dynamics given the lack of interactions with the soil matrix. While this catchment may sound unique given the dense drainage network, it was estimated that in Switzerland on average 28% of the agricultural area is directly connected to surface water and another 35% is indirectly connected through artificial structures ( Schönenberger & Stamm, 2021 ).…”
Section: Discussionmentioning
confidence: 99%
“…To determine the topographical catchment of each sampling site with respective crops and pesticide applications, we used a surface runoff connectivity model (Schönenberger and Stamm, 2021 ). The model is based on a digital elevation model (Swisstopo, 2019 ) with 2 × 2 m resolution and a D-infinity flow algorithm (Tarboton, 1997 ).…”
Section: Methodsmentioning
confidence: 99%
“…In contrast to other countries, roads and adjacent fields in Switzerland are less often drained to ditches, but to inlet and maintenance shafts of storm and tile drainage systems (Alder et al, 2015 ). In a model-based study on the national level, we found that around half of surface runoff from fields and the related pesticide load is expected to be transported to surface waters through such shafts (Schönenberger and Stamm, 2021 ; Schönenberger et al 2022 ). Similarly, another model-based study suggests that also the wash-off of spray drift deposited on roads through such shafts to surface waters may be a major pesticide transport pathway (Schönenberger et al, 2022).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation